Change in refraction after lens-sparing vitrectomy for rhegmatogenous retinal detachment and epiretinal membrane. Issue 32 (August 2016) - Iwase, Takeshi; Yamamoto, Kentaro; Yanagida, Kosei; Kobayashi, Misato; Ra, Eimei; Murotani, Kenta; Terasaki, Hiroko
Abstract : Abstract: The aim of this study was to compare changes in refraction following lens-sparing vitrectomy between patients with rhegmatogenous retinal detachment (RRD) and epiretinal membrane (ERM) and to investigate factors associated with the change in refraction. We reviewed medical records of 49 eyes of 49 patients with RRD (53.6 ± 7.8 years, mean ± standard deviation) and 24 eyes of 24 patients with ERM (50.9 ± 15.7 years) who underwent lens-sparing vitrectomy. Spherical equivalent refractive power was evaluated before and up to 18 months after surgery. The relationship between the change in refraction and several parameters was evaluated. A significant progressive myopic shift in refractive power was observed after vitrectomy in operated RRD and ERM eyes ( P < 0.001, P = 0.016, respectively), with no significant difference in fellow eyes. The refraction values observed at ≥3 and ≥12 months following vitrectomy were significantly different as compared with those observed at baseline in the RRD group ( P < 0.001) and the ERM group ( P < 0.05), respectively. The change in refraction between the RRD and ERM groups was significant ( P = 0.030). The multiple linear regression analysis showed that only age was significantly correlated with the change in refraction in RRD ( P = 0.018) and ERM ( P < 0.001) groups. The change in refraction was significantly and positively correlated with age in RRD ( r = −0.461, P = 0.001) and ERM ( r = −0.687, P < 0.001) groups. Following lens-sparing vitrectomy, cataract surgery was performed on 30 eyes after 0.89 ± 0.26 years in the RRD group and on 10 eyes after 1.11 ± 0.14 years in the ERM group; there was a significant difference in time to cataract surgery between the groups ( P = 0.007). Kaplan–Meier survival analysis demonstrated that there was a significant difference in the rate of cataract surgeries between the RRD and ERM groups ( P = 0.022). Following lens-sparing vitrectomy for RRD and ERM, a progressive myopic shift in refraction owing to nuclear sclerosis was observed. Core vitrectomy itself would cause a myopic shift of refraction. The only risk factor associated with cataract progression following lens-sparing vitrectomy is age for both types of patients. Abstract : Supplemental Digital Content is available in the text